Pengaruh Motivasi terhadap Pengembangan Karier Pegawai di Lembaga Pemasyarakatan Narkotika Kelas IIA Muara Beliti - Inelda Dwi Jayanti; Naniek Pangestuti (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
In the situation and condition of competency development that is growing rapidly, human resources (HR) must further improve their competencies, knowledge and abilities in the context of career development in a better direction. Therefore, this study aims to determine the effect of motivation on employee career development, especially in the Narcotics Correctional Institution Class IIA Muara Beliti. This research was conducted using quantitative descriptive method with the aim of knowing the effect between the independent variables and the dependent variable. The research data was obtained from the distribution of research questionnaires to 71 employees who became the research sample. From the results of the research that has been carried out, it shows that there is an influence of motivation on the career development of employees at the Class IIA Narcotics Correctional Institution Muara Beliti. This is based on the results of the sig value. of (0,000 < 0.05) and the value of tcount > ttable of (6,634 > 1,99495). The value of R Square shows that the motivation of employees in the Narcotics Correctional Institution Class IIA Muara Beliti is 38.9% in the study and 61.1% is influenced by variables from outside the study.